Reactualization of Marhaenism Principles to Promote Marginal Community’s Social Welfare - Pratama, Febri Fajar; Asyiah, Ai Kusmiati; Chandra, Deni (Universitas Pendidikan Indonesia, 2021)
Marhaenism is the principle of struggle for the Indonesian people driven by Sukarno in the early days of the national movement against imperialism of foreign nations. The oppression and capitalism of the bourgeoisie at that time became a crucial issue which Sukarno saw as something to be opposed. The marhaen, hereinafter became a term for those who are oppressed, destitute, and do not have the opportunity to prosper themselves. Socio-democracy, socio-nationalism, mass action and non-cooperation characterize the marhaen movement. In the end, marhaenism succeeded in becoming the distinctive ideology developed by Sukarno and inspired him in designing the basics of the formulation of Pancasila. However, after independence, problems related to poverty and the welfare of the community, especially the marginalized (marginalized) are still not over, so there is a need for a political strategy that leads to policy optimization by prioritizing the interests of the little people. So, the reactualization of the principle of marhaenism becomes relevant to be reviewed and echoed again. The purpose of this study is to provide an analytical (descriptive analytical) description of the reactualization of the principle of marhaenism using a qualitative approach.